The kings' list - Presley, Jade (Never list, 2026)
"They said the trials were over. They were wrong. I survived the Choosing. I claimed my mates. I became immortal. But the kings weren't finished with us yet. Four princes. Four thrones. And a final season designed to decide if we're worthy to rule. Every task is a test. Every smile is a lie. The people judge. The council votes. And the kings are waiting for us to fail. I was never meant to be queen. I was an Ashlander who broke into a palace searching for her sister. Now I stand beside the Legends of Chaos, holding power the kingdom fears and love fierce enough to burn it all down. To win the crowns, we'll have to survive the Kings' List. Failure isn't an option. Because this time, we're not just fighting for the throne--we're fighting for each other."--